Most frequent scenario for recurrent Candida vaginitis is strain maintenance with "substrain shuffling": demonstration by sequential DNA fingerprinting with probes Ca3, C1, and CARE2. - Lockhart, S R (1996)
The following three basic scenarios have emerged for the genetic relatedness of strains in recurrent vaginal candidiasis: strain maintenance without genetic variation, strain maintenance with minor genetic variation, and strain replacement. To test the frequency of each of the three scenarios, the genetic relatedness of Candida albicans isolates from each of 18 patients with recurrent infections was assessed by sequential DNA fingerprinting with the following three probes: the Ca3 probe; the C1 probe, a subfragment of the Ca3 probe which hybridizes to hypervariable genomic fragments; and the unrelated CARE2 probe. In each of the 18 patients with recurrent infections, the same strain was responsible for sequential infections, suggesting that the predominant scenario is strain maintenance. However, in 56% of these patients, the strain exhibited minor genetic variations in sequential infections. These changes were not found to be progressive. Rather, the changes suggest that substrains of an established infecting strain are shuffled in sequential infections. Results are also presented that in 45% of patients with recurrent infections, oral and vulvovaginal isolates were identical, in 35% they were highly related but not identical, and in 20% they were unrelated. These results differ markedly from those for commensal isolates simultaneously cultured from the oral cavity and vulvovaginal region of healthy individuals. Finally, it is demonstrated that in all eight cases in which C. albicans was isolated from both the male sexual partner of the patient with a recurrent infection and the patient, an isolate from the male partner was identical or highly related to the vulvovaginal strain. These results demonstrate that in patients with recurrent vulvovaginitis, a single strain usually dominates both in the different body locations of the patient and in the male partner and that it is maintained through sequential infections. However, in patients with recurrent infections, different substrains of the established clone dominate in an apparently random fashion, a process that we refer to as "substrain shuffling".